Identificação, modelagem, análise e estudo de medidas para o controle dos níveis de ruído gerado por compressores herméticos rotativos - Fagundes Neto, Marlipe Garcia (2012)
Noise is a physical agent of concern in any environment for human beings. Hermetic rotary compressors, present in various sectors, as a source of noise need continued research and development aimed at improving; and consequently a better quality of life to humankind. Due to the own kinematic compression process and combined with the large area of the housing, the noise spectrum of these compressors is quite complex. However, this study identifiy and analyze the contribution of various mechanisms of generation and transmission of noise from the compressor manufactured by Tecumseh. It was observed that low frequencies are controlled by kinematic mechanisms: electric motor and vane. Medium are controlled by the gas flow, valve, shaft and roller. The high frequencies are domain by friction. We noticed that the noise reduction is not a specific problem and needs multiple solutions, which together result in the mitigation of noise generated. Finally, a multibody model was developed. I showed good correlation with the real system.